(untitled) (Bangladesh Journal of Agricultural Research, 2014)
An experiment was conducted at the research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during October 2006 to May 2007 to evaluate the effects of zinc, boron, and molybdenum on the seed yield of carrot. The soil of the studied field was deficient in zinc, boron, and molybdenum and represents Salna Series of Shallow Red Brown Terrace under Madhupur Tract (AEZ-28). Four (4) levels each of zinc (0, 2.0, 4.0, and 6.0 kg/ha), boron (0, 1.0, 2.0, and 3.0 kg/ha) and molybdenum (0, 0.5, 1.0, and 1.5 kg/ha) were used to formulate 11 treatment combinations to observe their effects on the seed yield of carrot (cv. Bejo Shetal). A blanked dose of N120P54K150S20 kg/ha was also applied to nourish the crop. The experiment was laid out in a randomized complete block design with three replications. The seed yield of carrot was significantly increased due to integrated effects of zinc, boron and molybdenum. The highest seed yield (362.28 kg/ha) was found with Zn4.0B2.0Mo1.0 kg/ha combination, which was 283% higher over control. The maximum germination percentage (91.30) and vigor index (4.99) of seed was also recorded from the same treatment package and thus may be recommended for the production of carrot seed in the studied or alike area of the country. DOI: http://dx.doi.org/10.3329/bjar.v38i4.18869 Bangladesh J. Agril. Res. 38(4): 563-572, December 2013